Breast Cancer Patients at Dr. Zainoel Abidin Hospital Banda Aceh - Meildi, Maria; Arifki, Azwar; Razi, Fachrul; Darmi, Noer Faisal; Razi, Khalikul (CV. Publikasi Indonesia, 2025)
Breast cancer was the most common cancer-related death in women. Epidemiology reports the incidence to increase related to stage, histopathologic and subtype. Epidemiology reports in Aceh of breast cancer patients treated at Zainoel Abidin Banda Aceh Hospital are still limited. We want to report breast cancer patient profiles in Aceh. This study uses a quantitative descriptive approach by analyzing medical data of breast cancer patients recorded during 2021. The variables analyzed include age, age, location of cancer, histopathology type, grading and subtype of breast cancer performed. In this study, it was found that patients diagnosed with breast cancer were aged 36-50 years with images of 53 patients (37.86%) patients aged over 50 years and 14 (10%) patients aged under 36 years. The most common histopathology types were invasive ductal carcinoma 64%, and invasive lobular carcinoma 36%. Histopathology grading of breast cancer obtained the highest grade with grade III as many as 79 patients (56%). The most common subtype of breast cancer was triple negative. Breast cancer patients were most common at the age of 50 years old, histopathology was invasive ductal carcinoma, and the most common subtype of breast cancer was Triple Negative.